The dogs of Christmas - Cameron, W. Bruce (Forge, A Tom Doherty Associates book, 2013)
"While nursing a broken heart, Josh Michaels is outraged when a neighbor abandons his very pregnant dog, Lucy, at Josh's Colorado home. But Josh can't resist Lucy's soulful brown eyes, and though he's never had a dog before, he's determined to do the best he can for Lucy."--Provided by publisher.